Indoor Air Quality and Sick Building Syndrome in Selected Public Buildings in Shah Alam, Selangor - Ismaniza Ismail; Mohamad Solehin Zulkarnain; Ilyas Syafiq Darul Ridzuan; Yahya Thamrin; Nasrul Hamidin (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Indoor Air Quality (IAQ) is always associated with Sick Building Syndromes (SBS) despite the age of the buildings, particularly in buildings where indoor air pollutants may affect occupants’ health and productivity. This study assessed IAQ parameters and SBS symptoms in five selected public buildings aged 10 and above in Shah Alam, Selangor. Physical, chemical and biological parameters were measured, while structured questionnaires were completed by 87 respondents occupying the buildings. Most IAQ parameters were within the ranges of the Industry Code of Practice on IAQ (ICOP IAQ 2010), except for air velocity, formaldehyde and Total Volatile Organic Compound (TVOC) in two buildings. Statistical analyses showed no association between the building type and SBS occurrence, and no significant differences (p > 0.05) in air velocity, TVOC, CO2 or fungal count among the buildings. In order to reduce SBS risks and enhance SBS, the source of contaminants should be tackled and regular monitoring should be implemented to ensure compliance with IAQ limits.